2010
DOI: 10.3109/09637486.2010.529070
|View full text |Cite
|
Sign up to set email alerts
|

The effect of green tea and olive oil on the mutagenic activity of heterocyclic amines extracted from common food consumed in Saudi Arabia

Abstract: The effect of green tea (GT) and green tea with olive oil (GT+OL) as antioxidants on the formation and mutagenic activity of heterocyclic aromatic amines (HCAs) extracted from beef shawerma, grilled chicken and fried beef liver was examined. HCAs were extracted by blue rayon, analyzed as spiked and unspiked samples with high-performance liquid chromatography and its mutagenic response was assessed by Sallmonela typhimurium 100 in the Ames test. Surprisingly, GT and GT+OL augmented HCAs measured in beef shawerm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…6,7 The use of antioxidant compounds is considered a new promising strategy for minimizing HAA formation due to their free radical scavenging potential. 8 To date, the inhibitory potential of several natural antioxidants, for instance grape seed, 9 apple peel polyphenols, 10 green tea, 11 artichoke extract, 12 hawthorn extract, 13 blueberry, raspberry and strawberry extract, 14 on HAA formation have been investigated. Although the HAA content in salmon and various fish species has been investigated in previous studies, to the best of our knowledge the role of antioxidants for reducing HAA formation in salmon has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The use of antioxidant compounds is considered a new promising strategy for minimizing HAA formation due to their free radical scavenging potential. 8 To date, the inhibitory potential of several natural antioxidants, for instance grape seed, 9 apple peel polyphenols, 10 green tea, 11 artichoke extract, 12 hawthorn extract, 13 blueberry, raspberry and strawberry extract, 14 on HAA formation have been investigated. Although the HAA content in salmon and various fish species has been investigated in previous studies, to the best of our knowledge the role of antioxidants for reducing HAA formation in salmon has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Natural antioxidants contain a mixture of phytochemical compounds, which can inhibit the formation of HAAs. GTE at a lower level induced the formation of HAAs due to the pro‐antioxidant capacity depending on its concentrations and radicals (Awney, 2010). Weisburger et al (1994) determined that green tea had little effect on preventing the formation of MeIQx, but prompted the formation of PhIP in the model system.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, olive oil diets help in controlling blood pressure, glucose and lipids levels in diabetic patients [6] as well as in improving the immune function by attenuating the inflammatory process [7]. Rojas-Molina et al, [8] and Awney, [9] were tested some vegetable oils in the Drosophila wingspot test and found that extra-virgin olive oil (EVOO) was clearly not genotoxic, while soy oil showed a clear genotoxic activity.…”
Section: Introductionmentioning
confidence: 99%